Skin microbiome correlates with bioclimate and Batrachochytrium dendrobatidis infection intensity in Brazil’s Atlantic Forest treefrogs - Ruthsatz, Katharina; Lyra, Mariana L. [UNESP]; Lambertini, Carolina; Belasen, Anat M.; Jenkinson, Thomas S.; da Silva Leite, Domingos; Becker, C. Guilherme; Haddad, Célio F. B. [UNESP]; James, Timothy Y.; Zamudio, Kelly R.; Toledo, Luís Felipe; Vences, Miguel (Springer Nature, 2020)
In Brazil’s Atlantic Forest (AF) biodiversity conservation is of key importance since the fungal pathogen Batrachochytrium dendrobatidis (Bd) has led to the rapid loss of amphibian populations here and worldwide. The impact of Bd on amphibians is determined by the host's immune system, of which the skin microbiome is a critical component. The richness and diversity of such cutaneous bacterial communities are known to be shaped by abiotic factors which thus may indirectly modulate host susceptibility to Bd. This study aimed to contribute to understanding the environment-host–pathogen interaction determining skin bacterial communities in 819 treefrogs (Anura: Hylidae and Phyllomedusidae) from 71 species sampled across the AF. We investigated whether abiotic factors influence the bacterial community richness and structure on the amphibian skin. We further tested for an association between skin bacterial community structure and Bd co-occurrence. Our data revealed that temperature, precipitation, and elevation consistently correlate with richness and diversity of the skin microbiome and also predict Bd infection status. Surprisingly, our data suggest a weak but significant positive correlation of Bd infection intensity and bacterial richness. We highlight the prospect of future experimental studies on the impact of changing environmental conditions associated with global change on environment-host–pathogen interactions in the AF.